Elderly population and labour market stabilization in Europe: The case of Slovenia - Rasto Ovin; Marko Divjak; Živa Veingerl Čič; Anita Maček (Naše gospodarstvo / Our Economy, 2021)
The growing share of the retired population in Europe worsens the balance of the social costs as social consensus in most European countries rests on extensive social transfers for this population group. With its 25% share in GDP and 50% share in social transfers, the European (continental) model is indeed not sustainable when compared globally. The current prevailing model of "rejuvenation" of the labour market through immigration did not prove as a sustainable solution. The same is valid for the perspective of fast technological change. It is based on filling the labour market with low-paid jobs enabling host economies to leave aside the imperative permanent change in the labour market structure. This paper discusses the case of Slovenia and tries to search the reasons for the absence of elderly population in the labour market in this country. Based on the data comparison and disposable studies, authors try to identify the main issues when endeavouring to keep elderly population in the labour market.
Keywords: M50; 330; elderly population economic activity; labour market; HRM gap in Slovenia